Подавление возмущений в системах управления с внутренними моделями: структурный подход - Любчик, Л. М. (Видавництво Львівської політехніки, 2011)
The problem of unmeasurable disturbance rejection in multivariable system is considered based on Internal Model approach. The control structure including disturbance observer is investigated and conditions of disturbance decoupling compensator existence are suggested.
Keywords: disturbance rejection; decoupling compensator; internal model control; model matching; unknown-input observer